Stable H-bond networks are crucial for selective CDK4 inhibition revealed from comprehensive in silico investigation. (August 2022) - Zhang, Zhigang; Hu, Baichun; Joseph, Johnson; Wang, Ying; Mao, Jianping; Zhang, Haoyu; Ma, Qi; Zhang, Yaoliang; Wang, Jian
Abstract: CDK1 and CDK4 are highly similar isoforms but with apparently diverse cellular functions, which makes it fundamental to discover selective CDK4 inhibitors that could accurately control the process of cell cycle of the specific organization so as to restore normal physiological state. In current research, interaction modes of CDK1 and CDK4 inhibitors were investigated through combined in silico strategies to elucidate the selectivity mechanism against CDK4 over CDK1, revealing that H-bond networks formed with key amino acids such as LYS33 and LEU83 of CDK1 and VAL93 of CDK4 are crucial for CDK4 selective inhibition, which would provide a theoretical basis for the design of selective CDK4 inhibitors. Graphical Abstract: ga1 Highlights: The interactions between CDK isoforms, and their selective inhibitors are investigated to elucidate the selectivity mechanism. Crucial amino acids involved in molecular interaction are explored, to reveal the main contributor to molecular interactions. A variety of methods, including MD simulation, ASM, QM/MM calculation, etc., were employed to verify the hypothesis.